2020
DOI: 10.55320/mjz.47.3.703
|View full text |Cite
|
Sign up to set email alerts
|

Medical School Admissions: A Review of Global Practices, Predictive Validity, and Practice Points for Africa.

Abstract: Background: Processes for selection of candidates into medical schools vary globally. Knowledge of the predictive validity of a selection method is important for policy revision. Aim: To survey the practices used by medical schools to select students and their predictive validity. Methods: Search terms developed from the research problem were used to search Google Scholar, PubMed, and Educational Resources Information Centre (ERIC). These were “medical school,” “predictive validity,” “success,” “ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…New schools can be innovative regarding student admission policies. In a review of medical school global admissions policies, researchers at Mulungushi University in Zambia suggested that schools in Africa should consider academic as well as non-academic elements in medical school admissions (Ezeala et al, 2020). While academic excellence may predict achievement in the pre-clinical stage, non-academic attributes were reported to be predictive of success in the clinical stages of training (Ezeala et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…New schools can be innovative regarding student admission policies. In a review of medical school global admissions policies, researchers at Mulungushi University in Zambia suggested that schools in Africa should consider academic as well as non-academic elements in medical school admissions (Ezeala et al, 2020). While academic excellence may predict achievement in the pre-clinical stage, non-academic attributes were reported to be predictive of success in the clinical stages of training (Ezeala et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In a review of medical school global admissions policies, researchers at Mulungushi University in Zambia suggested that schools in Africa should consider academic as well as non-academic elements in medical school admissions (Ezeala et al, 2020). While academic excellence may predict achievement in the pre-clinical stage, non-academic attributes were reported to be predictive of success in the clinical stages of training (Ezeala et al, 2020). Using selection instruments based on a variety of factors, including socioeconomic status, can help select the most fitting candidates and fulfill a school's social obligation to include students from a variety of backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…Student selection and admission policies and practices, according to many researchers, should be designed to ensure a good match between the applicant's abilities and aptitudes and the demands of the program. [1][2][3][4] However, there is little known about how Ethiopian Higher Education admission and placement policies and procedures ensure quality education in the face of rapid higher education expansion and high student enrollment.…”
Section: Introductionmentioning
confidence: 99%